PROFESSIONAL FOSTER FAMILY: SOCIAL AND PSYCHOLOGICAL CHARACTERISTICS OF A SPECIAL SMALL SOCIAL GROUP - A. Makhnach (Вестник университета)
The analysis of the concept of «professional foster family» has been presented. The stages of the formation of this social phenomenon in studies of orphanhood in Western and Russian psychology have been described. The сhanging the focus of study has been noted from the characteristics of an orphan child in orphanages to his upbringing in a foster family, for the family as a whole. The process of forming a problem field and conceptualization of this concept in a historical context has been analyzed. The issue of the professional description of the activities of foster parents has been considered. Attention has been payed to the paradigm shift in the study of the foster family with a deficiency to its resourcing and resilience.